Pemeliharaan Allah Di Masa Pandemi COVID-19: Sebuah Refleksi Teologis Berdasarkan Kitab Ester - Robi Prianto; Yohanes Hasiholan Tampubolon (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
The Covid-19 pandemic has resulted in the presence of various theological reflections. One of the topics discussed was about God's providence. This paper will present a theological reflection based on the book of Esther on God's providence. This study uses a qualitative approach with a descriptive exegesis approach by focusing on the structure of the book of Esther. This study found that although there is no name